Fabrication and characterization of bioactive nanoemulsion-based delivery systems - Yilmaz, Azime; Meral, Raciye; Kabli, Mohammad; Ermis, Ertan; Akman, Perihan Kubra; Dertli, Enes; Taylan, Osman; Sagdic, Osman; Yilmaz, Mustafa Tahsin (EMERALD GROUP PUBLISHING LTD, 2021)
In this work, a nanoemulsion-based delivery system was developed by encapsulation of different concentrations (0.50%, 0.75% and 1.00% v/v) of oregano essential oil (OEO) within poly(vinyl alcohol). The delivery systems (OEO-loaded nanoemulsion systems (NESs)) were characterized in terms of size distribution, zeta potential and thermal, molecular, microstructural and antifungal properties. The average droplet diameter values were determined to be within the range 70-75 nm, while zeta potential values within the range 3.13-19.90mV were recorded. An increase in the OEO concentration did not affect the size distribution of nanoemulsions. Change in the concentrations showed no visible differences in Fourier transform infrared spectra. However, for concentrations of 0.50, 0.75 and 1.00%, endothermic peak temperatures were recorded as 94, 105 and 117 degrees C, respectively. The antifungal activity of NESs against the mycelial growth of Aspergillus niger was evaluated, revealing a significant enhancement in the antifungal activity in comparison with that of free OEO. The zone diameter of mycelial growth could be reduced by around 20, 55 and 65% using NESs at levels of 0.50, 0.75 and 1.00% v/v, respectively, over 6 days of incubation. The results of this study revealed the stronger antifungal efficiency of OEO by its encapsulation into NESs as compared with that of free OEO.
Keywords: characterisation; molecular properties; nanobiomaterial; OREGANO ESSENTIAL OIL; PLANT ESSENTIAL OILS; ANTIFUNGAL ACTIVITY; ANTIMICROBIAL ACTIVITY; CLOVE OIL; IN-VITRO; ASPERGILLUS; CHITOSAN; EUGENOL; ANTIOXIDANT; Materials Science